Influence of water on granite tunnel rockburst by AE - Zhang Yanbo; Liu Xiangxin; Yao Xulong; Liang Peng (Федеральное государственное автономное образовательное учреждение высшего образования «Дальневосточный федеральный университет», 2016)
Rock mass at site has usually been in water-rich environments for a long periods. In order to study the effects of water on Granite tunnel rockbursts, natural and water-saturated specimens have been took experiment here. Rockbursts on roadways were monitored using the acoustic emission (AE) system from PCI-2. Results showed that water invasion reduced the compressive strength and elasticity of the rock, at rates of 10.8% and 18.3%. When the rock surrounding the roadway came into contact with water, the fracture morphology and energy dissipation methods changed, and the splitting intensity of surrounding rock on both the left and right sides were relieved. The AE information of Granite saturated with water during its rockburst evolution process was more enriched than that of natural Granite. The quiet periods in AE were shorter than in natural rock and the large electrical events appeared earlier. These results all suggested that the injection of water into rocks near roadways changes the rate of rock fracture formation and reduces energy storage, thereby, preventing and controlling rockburst.
Keywords: WATER; ROADWAY ROCKBURST; BIAXIAL; AE; ВОДА; УДАРООПАСНОСТЬ; ДВУХКООРДИНАТНЫЙ; СЕЙСМОАКУСТИЧЕСКАЯ ЭМИССИЯ; 622.011:622.83